A20 as a Potential Therapeutic Target for COVID‐19 - Yongyao Wu; Lilan He; Rong Li; Jiuxuan Li; Qing Zhao; Bin Shao (Immunity, Inflammation and Disease)
ABSTRACT Background Coronavirus disease 2019 (COVID‐19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), is a major concern due to its astonishing prevalence and high fatality rate, especially among elderly people. Patients suffering from COVID‐19 may exhibit immunosuppression in the initial stage of infection, while a cytokine storm can occur when the disease progresses to a severe stage. This inopportune immune rhythm not only makes patients more susceptible to the virus but also leads to numerous complications resulting from the excessive production of inflammatory factors. A20, which is widely accepted as a pivotal regulator of inflammation, has been shown to be implicated in the processes of antiviral responses and immunosuppression. Thus, A20 may participate in regulating the pathological processes of COVID‐19. Methods This narrative literature review summarizes recent evidence on the mechanisms of A20 in regulating the pathological processes of COVID‐19. We also downloaded single‐cell RNA‐seq data sets from healthy individuals and patients with varying severities of COVID‐19 from the NCBI GEO database to further dissect A20's regulatory mechanisms of these intricate cytokine pathways that are closely associated with SARS‐CoV‐2 infection. Results A20 might be one of the most critical anti‐infectious and anti‐inflammatory factors involved in the pathogenesis of COVID‐19. It effectively suppresses the immune damage and inflammatory storm caused by viral infection. Conclusions Understanding the relationship between A20‐regulated signaling pathways and pathological processes of COVID‐19 can provide insight into potential targets for intervention. Precise regulation of A20 to induce antiviral activity and an anti‐inflammatory response could mediate the pathogenesis of COVID‐19 and could become an effective treatment.